Fluid deficiency in elderly patients and causing factors - طنوس سائر موريث (Latakia University Journal -Medical Sciences Series, 2022)
Elderly people are more susceptible to dehydration and lack of fluids, as a result of aging, decreased thirst, taking certain medications to treat chronic diseases, lack of neuro-cognition, and other factors, leading to the presence of symptoms of fluid deficiency ranging in severity from annoyance to life-threatening. In view of the important nursing role in managing this problem, the current descriptive study was conducted to identify fluid deficiency in 50 elderly patients and the factors causing it, they were selected using the convince sample method from the patients attending the clinics department at Tishreen University Hospital, and the data were collected using a questionnaire developed by the researcher. The results showed that the largest proportion of the elderly patients consumes daily 3-6 glasses of fluids, specifically water, and that the weakness of the ability to exert effort is the most common symptom in more than three quarters of them. The highest percentage were feeling thirsty and dry mouth, and nearly half of them had wet mucous membranes when examined, and the return of capillary refill indicates a lack of fluids in more than half of them. Approximately three-quarters of the elderly were in an abnormally hydrated state. In terms of factors causing fluid deficiency, depression or mood changes were the most common causes of fluid deficiency. In addition, there is a statistically significant relationship between hydration status and both dysphagia / digestive disorders and lack of available fluids. The study recommended the design of educating programs for the elderly to maintain the natural level of water in their body, and to provide adequate information to health care providers about methods of early diagnosis of fluid deficiency in the elderly, and to identify its symptoms and manage it optimally, and to conduct similar research on larger samples that include elderly people in all places in the community such as health centers, hospitals and homes..